Pendidik dalam Perspektif Al-Qur’an - sada, Heru Juabdin (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2015)
Education in Islam is a complete guidance is not merely connotes authoritative teaching of the educational workers are educators, but also with appropriate guidance to Islamic teachings, the students have ample movement space in mengatualisasikan potential they have. Educators is a very important component in the education system, for educators as a bridge for learners reach predetermined goals,  along with  other components  related.  Educators have  a  noble position, educators are expected to be uswatun hasanan that could provide an example for students, as well as guiding and motivating learners in order to meet the future better.